Inappropriate use of commercial Antinuclear Antibody Testing in a community-based US hospital: a retrospective study. Issue 4 (1st January 2016) - Mohammed, Abdul S.; Boddu, Prajwal; Mael, David; Samee, Mohammed; Villines, Dana
Abstract : Healthcare providers use antinuclear antibodies (ANAs) to screen and diagnose patients with autoimmune diseases. In the recent years, commercial multiplex ANA kits have emerged as a convenient and fast diagnostic method. Diagnostic testing should follow sequenced algorithms: initial screen followed by specific antibody analysis. Second-level testing as an initial screen for autoimmune disease is inappropriate. We reviewed 68 patients with ANA comprehensive panels over a 6-month period from May 2015 to October 2015. We assessed appropriateness and estimated incurred losses from inappropriate testing. We found 92.6% (63 out of 68) of the ANA comprehensive panel results to be negative. Incurred losses from inappropriate ANA comprehensive panel testing were 66, 000. Physicians should become familiar with ANA-sequenced diagnostic algorithms to avoid unnecessary higher level testing.